Pengadaan koleksi electronic resources di Perpustakaan Universitas Islam Negeri Sunan Kalijaga Yogyakarta - Ahmad Syafii; Imam Machali; Nur Hidayanto Pancoro Setyo Putro (Jurnal Kajian Informasi dan Perpustakaan, 2021)
University Libraries are sources of electronic resources that are accessible to users. The literature search results show that few studies discuss electronic resource procurement in Indonesian libraries. This article aimed to determine the procurement of electronic resources collections at the Sunan Kalijaga State Islamic University (UIN) Library. The study used a qualitative approach with a descriptive research method conducted at the UIN Sunan Kalijaga Library. Data collection techniques used structured interviews with seven informants. The analysis results showed seven main findings in the procurement process for collecting electronic resources: the target, budgeting, user specifications, single sign-on authentication, the right team, content duplication, and communication with vendors. The library analyzed the contents of electronic resources to be purchased. Libraries use Ministry and Institutional Work Plan and Budget (RKAKL) funds in their budgeting. Subscriptions to electronic resources are specially for undergraduate and postgraduate students. The Single Sign-On authentication system used is EZproxy. The Procurement team consists of the head of the library, deputy head of the library, technical service coordinator, and general reference coordinator. The duplication-checking process is carried out based on the subject. In the communication process with vendors, the team has coordinated well. The research findings contribute to Indonesia's electronic resources procurement management practices.